Solve for v (3v+2)-(v+1)=v+(2v+3)

Math
(3v+2)-(v+1)=v+(2v+3)
Simplify (3v+2)-(v+1).
Tap for more steps…
Simplify each term.
Tap for more steps…
Apply the distributive property.
3v+2-v-1⋅1=v+2v+3
Multiply -1 by 1.
3v+2-v-1=v+2v+3
3v+2-v-1=v+2v+3
Simplify by adding terms.
Tap for more steps…
Subtract v from 3v.
2v+2-1=v+2v+3
Subtract 1 from 2.
2v+1=v+2v+3
2v+1=v+2v+3
2v+1=v+2v+3
Add v and 2v.
2v+1=3v+3
Move all terms containing v to the left side of the equation.
Tap for more steps…
Subtract 3v from both sides of the equation.
2v+1-3v=3
Subtract 3v from 2v.
-v+1=3
-v+1=3
Move all terms not containing v to the right side of the equation.
Tap for more steps…
Subtract 1 from both sides of the equation.
-v=3-1
Subtract 1 from 3.
-v=2
-v=2
Multiply each term in -v=2 by -1
Tap for more steps…
Multiply each term in -v=2 by -1.
(-v)⋅-1=2⋅-1
Multiply (-v)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1v=2⋅-1
Multiply v by 1.
v=2⋅-1
v=2⋅-1
Multiply 2 by -1.
v=-2
v=-2
Solve for v (3v+2)-(v+1)=v+(2v+3)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top